Main Stages Of Pottery Production (A Case Study Of The Rishtan Pottery Center In The Late 19th And Early 20th Centuries) - Bobir Odilov (Frontline Social Sciences and History Journal, 2026)
This article analyzes the traditional technological processes of ceramic production in the Rishtan pottery school based on historical and ethnographic sources. The study examines local raw material resources, clay preparation techniques, methods of shaping pottery, drying technologies, preparation of engobe (base coating) and glaze layers, as well as firing processes in traditional kilns. Particular attention is paid to ethno-territorial factors that influenced the quality, form, and artistic characteristics of Rishtan ceramic products. The research contributes to a deeper understanding of the place of the Rishtan pottery school within the broader system of Central Asian craft traditions and highlights the distinctive technological knowledge preserved by local artisans.